The Role of Information and Communication Technologies in Authoritarian States: A Comparative Analysis of China and Tunisia - Kulmurza, A. (MAQSUT NARIKBAYEV UNIVERSITY (KAZGUU) International School of Economics, 2023)
This thesis examines the role of ICTs in authoritarian states, using the cases of Tunisia and China as examples. The paper emphasizes that authoritarian states use ICTs as a tool for political control and Internet surveillance. The aim of this paper is to analyze the impact of ICTs on authoritarian governments and to comprehend their role in mass protests and democratization. The study considers sources such as statistical indicators, articles, news publications, and websites. This thesis uses a qualitative research method, along with a comparative case analysis between Tunisia and China. The most similar systems method was also used to investigate the similarities and differences among the two selected countries, which led to different outcomes. The executed paper can be considered a detailed source for understanding the experiences of Tunisia and China in terms of identifying the factors that, despite certain similarities in the use of ICTs, led to different political changes.
Keywords: Information and communication technologies (ICTs); Authoritarian regimes; Internet surveillance; Political control; Mass protests; Democratization; Comparative case study; Tunisia; China